Endoscopic band ligation combined with argon plasma coagulation versus band ligation alone for eradication of esophageal varices - Ali Ghweil; Shamarden Bazeed; Mohamed Alsenbsy; Heba Saleh; Mohamed El Kassas; Bahaa Abbas; Gamal Esmat; Hamdy Moustafa (Wolters Kluwer Medknow Publications, 2016)
Background and aim Bleeding esophageal varices are the gravest complications of liver cirrhosis, with a high mortality. Although band ligation is considered the gold standard in the eradication of varices, it is plagued by a high recurrence rate after variceal eradication. The aim of the study was to assess safety and efficacy of endoscopic band ligation plus argon plasma coagulation (APC) versus endoscopic band ligation alone for the prevention of variceal recurrence and rebleeding. Patients and methods This prospective randomized comparative study was carried out on 100 patients admitted to Tropical Medicine and Gastroenterology Department, Qena University Hospital, during the period from March 2012 to complete follow-up on March 2014. Patients were randomized into two groups: group 1 included 50 patients who were subjected to endoscopic band ligation plus APC, and group 2 included 50 patients who were subjected to variceal band ligation. Results On comparing the results of the two groups as regards the incidence of variceal recurrence during the follow-up period, combined treatment group with band ligation plus APC had a significant low recurrence rate in comparison with band ligation alone treated group. As regards post-treatment complications in the combined treated group, there was transient fever (≥38°C) in 36% of patients, retrosternal pain (5-7 days) was reported in 20% cases, and bleeding during argon application occurred in one patient 2%. The development of severe complications did not occur in any of the patients. Mortality was reported in 10 cases in group 1 (three cases died by causes not related to liver disease). Conclusion Combined band ligation plus APC is safe and effective in prevention of variceal recurrence and rebleeding. The reported side effects were mild and reported mainly in older patients with child class C.